Decentralised H∞ finite-time control equation of large-scale switched systems using robust performance minimisation. Issue 10 (26th July 2016) - Han, Lu; Xiao, Jian; Qiu, Cunyong; Huang, Jingchun
Abstract : Many actual engineering applications can be modelled as large-scale switched system, while switching behaviours often occur in some short finite time intervals; thus, it is significant to ensure the finite-time boundedness of large-scale switched system in practical terms. In this paper, the problems of finite-time stability analysis and stabilisation for large-scale switched system are addressed. First, considering different switching signals for subsystems, the concepts of decentralised finite-time boundedness (DFTB) and decentralised finite-time H ∞ controllers are introduced, which focus on the dynamical transient behaviour of large-scale switched system during finite intervals. Under these concepts, several sufficient conditions are given to ensure a class of large-scale systems decentralised finite-time stable based on the decentralised average dwell times, and then the results are extended to H ∞ finite-time boundedness of large-scale switched system. Finally, based on the results on DFTB, optimal decentralised H ∞ controllers and average dwell times are designed under the minimum value of H ∞ performance. Numerical examples are given to illustrate the effectiveness of the proposed approaches in this paper.